2022
DOI: 10.3390/transplantology3020016
|View full text |Cite
|
Sign up to set email alerts
|

One Step at a Time: A Pediatric Case of Primary Two Staged Liver Transplantation in a Child with ESLD

Abstract: Toxic liver syndrome is a rare condition with multiorgan failure in end-stage liver disease (ESLD), and a two-stage LT following hepatectomy with a prolonged anhepatic phase is an accepted approach to bridge to transplant. This primary approach has not been described for toxic liver syndrome in children with ESLD. We report a 6-year-old boy who developed toxic liver syndrome with multiorgan failure while awaiting LT for ESLD from biliary atresia and failed Kasai at the age of 2 years. Deemed too sick to transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Further details of the characteristics of each study can be found in Table 4 . In successful cases, the systemic inflammatory response attributed to primary nonfunction seemed to improve during the initial anhepatic state [ 9 13 , 21 , 25 28 , 32 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further details of the characteristics of each study can be found in Table 4 . In successful cases, the systemic inflammatory response attributed to primary nonfunction seemed to improve during the initial anhepatic state [ 9 13 , 21 , 25 28 , 32 34 ].…”
Section: Discussionmentioning
confidence: 99%